Morphological characters, flowering and seed germination of the Indonesian medicinal plant Orthosiphon aristatus - SHALATI FEBJISLAMI; ANI KURNIAWATI; MAYA MELATI; YUDIWANTI WAHYU (Biodiversitas Journal of Biological Diversity, 2019)
Febjislami S, Kurniawati A, Melati M, Wahyu Y. 2019. Morphological characters, flowering and seed germination of the Indonesian medicinal plant Orthosiphon aristatus. Biodiversitas 20: 328-337. Orthosiphon aristatus (Blume) Miq is a popular medicinal plant in Southeast Asia. The morphological variation of O. aristatus is narrow and information on flowering and seed germination is limited. This study aimed to determine the morphological characters, flowering and seed germination of O. aristatus. The study was conducted on 19 accessions (ex situ collections) of O. aristatus from West, Central and East Java. It was found that the differences in morphological and flowering characters were mainly based on shape and color. The dominant stem color is strong yellowish green mixed with deep purplish pink in different proportions. The dominant leaf shape was medium elliptic. O. aristatus flower has three kinds of colors: purple, intermediate and white (the most common color). O. aristatus has heterostyled flower with a long-styled morph. The stigma has two shapes: open and close (the dominant shape). The open and close stigma was found in Tuban accession, the open stigma was found in Pamekasan accession. O. aristatus accessions have a narrow diversity of 84% similarity rate. O. aristatus started flowering at 4-5 weeks after planting and blooming 2-3 weeks later. O. aristatus seeds begin to germinate on the fourth day and take about eight days to grow from seedling to become complete sprouts. Count I ranged from day 5-6 and count II on days 10-11. Tuban accession has the highest germination rate of 72.97%. The results of this research can be considered as new information, regarding information about the diversity of morphological, flowering characters and the ability of O. aristatus seed to germinate.